2016
DOI: 10.1371/currents.dis.29e4c0c810db47d7fd8d0d1fb782892c
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Needs and Concerns among Pregnant Women During and after Typhoon Haiyan (Yolanda)

Abstract: Introduction: Pregnant and postpartum women are especially vulnerable to natural disasters. These women suffer from increased risk of physical and mental issues including pregnant related problems. Typhoon Haiyan (Yolanda), which hit the Philippines affected a large number of people and caused devastating damages. During and after the typhoon, pregnant women were forced to live in particularly difficult circumstances. The purpose of this study was to determine concerns and problems regarding public health need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 32 publications
0
24
0
1
Order By: Relevance
“…Women Are the Primary Water Purveyors, Particularly in the Developing Regions of the World Largely, the identified observational studies ( Table 1) emphasized issues in accessing clean water among women and girls, and described that a lack of clean water and water resources negatively contributed to women and girl's health and quality of life (Doherty et al, 2007;Bornman et al, 2012;Sato et al, 2016;Gaspar et al, 2017;Vos et al, 2017;Angoua et al, 2018;Prado et al, 2019). Studies which considered gender likewise revealed a lack of access to improved water for both men and women alike (Ugbomoiko et al, 2009;Al-Delaimy et al, 2014;Atalabi et al, 2016;Holvoet et al, 2016;Akombi et al, 2017;Baker et al, 2018).…”
Section: Synthesized Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…Women Are the Primary Water Purveyors, Particularly in the Developing Regions of the World Largely, the identified observational studies ( Table 1) emphasized issues in accessing clean water among women and girls, and described that a lack of clean water and water resources negatively contributed to women and girl's health and quality of life (Doherty et al, 2007;Bornman et al, 2012;Sato et al, 2016;Gaspar et al, 2017;Vos et al, 2017;Angoua et al, 2018;Prado et al, 2019). Studies which considered gender likewise revealed a lack of access to improved water for both men and women alike (Ugbomoiko et al, 2009;Al-Delaimy et al, 2014;Atalabi et al, 2016;Holvoet et al, 2016;Akombi et al, 2017;Baker et al, 2018).…”
Section: Synthesized Findingsmentioning
confidence: 99%
“…A multitude of studies focused on women and girls and demonstrated that women practiced poor sanitation, hygiene, and MHM practices, largely due to lacking resources. Sanitation facilities were commonly cited to not be safe, clean, and accessible (Kwiringira et al, 2014;Sato et al, 2016;Khan et al, 2017;Aluko et al, 2018;Angoua et al, 2018;Dendup et al, 2018;Desalegn et al, 2018;Njuguna, 2019;Winter et al, 2019). Basic needs, such as soap and washing facilities, and hygienic products, such as toothpaste were documented as hygiene barriers (Budhathoki et al, 2018;Lubon et al, 2018).…”
Section: Women Face Unique Wash and Mhm Challengesmentioning
confidence: 99%
See 3 more Smart Citations